2004
DOI: 10.1111/j.1469-0691.2004.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fusarium spp. in fungal keratitis

Abstract: Members of the filamentous fungal genus Fusarium are among the agents most frequently causing keratomycosis in humans. Fusarium keratitis is most common among agricultural workers in geographical regions with hot, humid, tropical or semi-tropical climates, but can occur more rarely in countries with temperate climates, such as Hungary. Keratitis is usually treated with a topical antifungal agent, sometimes in combination with sub-conjunctival injections and/or antimycotic agents, but therapeutic keratoplasty m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 24 publications
1
64
0
8
Order By: Relevance
“…Less frequently, the infection may occur as a result of skin breakdown, such as burns and wounds (74), or the presence of foreign bodies, such as keratitis in contact lens wearers (23), which at times causes outbreaks of fusarial keratitis (16). Peritonitis in patients receiving continuous ambulatory peritoneal dialysis has also been described (34,52,92).…”
Section: Epidemiology and Clinical Spectrum Of Fusariosismentioning
confidence: 99%
See 2 more Smart Citations
“…Less frequently, the infection may occur as a result of skin breakdown, such as burns and wounds (74), or the presence of foreign bodies, such as keratitis in contact lens wearers (23), which at times causes outbreaks of fusarial keratitis (16). Peritonitis in patients receiving continuous ambulatory peritoneal dialysis has also been described (34,52,92).…”
Section: Epidemiology and Clinical Spectrum Of Fusariosismentioning
confidence: 99%
“…Keratitis is usually treated with topical antifungal agents, and natamycin is the drug of choice (23). More recently, successful treatment with topical and oral voriconazole has been reported (13).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…F. solani is also the most common species in fusarial keratitis (5,9,24,25). Molecular phylogenetic studies have shown that the more commonly reported fusarial pathogens represent species complexes and cannot be identified to the species level by traditional morphological methods alone (21,24,25,38).…”
mentioning
confidence: 99%
“…La queratitis micótica representa una de las formas de queratitis más difíciles en su diagósitco y tratamiento, constituyendo un problema oftalmológico importante que puede llevar incluso a la pérdida de la visión (5,6) Lesiones traumáticas con ramas, espinas u otros elementos de orígen vegetal no sólo pueden provocar úlceras o erosiones corneales, sino también contaminación con propágulos fúngicos que pueden repro-ducirse y generar una importante reacción inflamatoria y necrosis (7,8). Estos datos coinciden con nuestro estudio, donde la mayor parte de los pacientes (8/10) presentaron lesiones con ramas o espinas previo a la infección fúngica.…”
Section: Discussionunclassified